Inhibition of phytopathogenic fungi on selected vegetable crops by catechins, caffeine, theanine and extracts of Camellia sinensis (L.) O. Kuntze - Labuschagne, Nico (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2008.